A Retrospective Study of Combined Cardiac and Carotid Surgery - Fabrizio Sansone; Edoardo Zingarelli; Giuseppe Punta; Stefano Del Ponte; Gianluca Bardi; Roberto Flocco; Piergiuseppe Forsennati; Francesco Parisi; Guglielmo Mario Actis Dato; Andrea Gaggiano; Emanuele Ferrero; Andrea Viazzo; et al. (Archives of Clinical and Experimental Surgery, 2012)
Introduction: A combined carotid endarterectomy (CEA) and cardiac procedure has higher early risk of stroke than isolated CEA because of the widespread atherosclerosis in patients selected for simultaneous procedures. In this retrospective study, we review the results of combined coronary artery bypass grafting (CABG) and carotid endarterectomy (CEA) procedures. Materials and methods: Between January 2000 and December 2007, 91 patients with a mean age of 69.2+6.6 (24/67 female/male) underwent combined operations (CEA-CABG) on cardiopulmonary bypass (CPB) as elective surgery. The study population was divided, as follows: Group A: 83 patients (91.2%) had both venous and arterial revascularization; Group B: 8 patients (8.8%) had total arterial revascularization. CEA was performed in case of stenosis more than 80% and always before cardiac operation. These techniques were used: standard procedure (54.8%), eversion (39.2%), patch enlargement (6%). Immediately after the vascular procedure, CABGs were performed through median sternotomy. The mean EUROscore was 6.9+2.5%. Results: All neurological complications were in the group who underwent both venous and arterial revascularization (Group A), where a proximal anastomosis was made. All complications and deaths were in group A. Six patients had stroke (6.6%) and 2 had acute myocardial infarction (AMI) (2.2%). There were 8 in-hospital deaths (8.8%) and 1 late death (for stroke after five months). Conclusions: In our center, the incidence of stroke in simultaneous cardiovascular procedures was 5.5 times greater than in isolated cardiac or vascular procedures, which was probably related to the widespread vessels disease. An aortic cross clamp and surgical procedure on the ascending aorta are relevant risk factors for developing neurological events; much attention should be paid to aortic manipulation. In the sub-group who underwent total arterial revascularization with associated CEA procedures, we had no neurological events. A partial cross clamp and proximal anastomosis are relevant risk factors for developing neurological events. Therefore, in combined operations (CEA associated with CABG), it is probably more favourable performing a total arterial revascularization, avoiding partial ascending aortic clamping. [Arch Clin Exp Surg 2012; 1(4.000): 201-205]